Bioengineered biochar as smart candidate for resource recovery toward circular bio-economy: a review. Issue 2 (20th December 2021) - Liu, Hong; Kumar, Vinay; Yadav, Vivek; Guo, Shasha; Sarsaiya, Surendra; Binod, Parameswaran; Sindhu, Raveendran; Xu, Ping; Zhang, Zengqiang; Pandey, Ashok; Kumar Awasthi, Mukesh
ABSTRACT: Biochar's ability to mediate and facilitate microbial contamination degradation, as well as its carbon-sequestration potential, has sparked interest in recent years. The scope, possible advantages (economic and environmental), and future views are all evaluated in this review. We go over the many designed processes that are taking place and show why it is critical to look into biochar production for resource recovery and the role of bioengineered biochar in waste recycling. We concentrate on current breakthroughs in the fields of engineered biochar application techniques to systematically and sustainable technology. As a result, this paper describes the use of biomass for biochar production using various methods, as well as its use as an effective inclusion material to increase performance. The impact of biochar amendments on microbial colonisation, direct interspecies electron transfer, organic load minimization, and buffering maintenance is explored in detail. The majority of organic and inorganic (heavy metals) contaminants in the environment today are caused by human activities, such as mining and the use of chemical fertilizers and pesticides, which can be treated sustainably by using engineered biochar to promote the establishment of a sustainable engineered process by inducing the circular bioeconomy. GRAPHICAL ABSTRACT: uf0001